Using inulin fiber supplementation with MyPlate recommendations promotes greater weight loss in obese women - Salmean, Younis A (Progress in Nutrition, 2020)
Obesity is a major public health problem in developed countries.  The obesogenic environments we live in today create unfavorable conditions to normalize body weights. Methods: The study was a simple randomized intervention study with twelve obese women (mean ± SD, aged 22.6 ± 3.6 y), and BMI ≥30 kg/m2. Participants were randomly assigned to either recommendation (R) only group (n=6), or recommendations with fiber (R-ITF) group (n=6). The guide contained recommendations on how to lose weight based on the United States Department of Agriculture’s (USDA) MyPlate published recommendations. The R-ITF group received a six-week supply of ITF along with the printed guide, while the R group received only the guide. Each participant receiving the supplement was instructed to consume 7g of inulin-type fructant fiber (ITF) three times a day before meals (21 g/d in total). Pre and post intervention measurements of weight, height, BMI and a 24 h dietary recall were collected. Results: The R-ITF lost significant weight compared to pre-intervention weight (89.2 ± 10.2 kg vs. 87.4 ± 9.9 kg, p0.05). The R-ITF group consumed significantly less energy compared to its pre-intervention energy intake from 1947 ± 129 kcal to 1742 ± 109 kcal, p